Conscription in Myanmar: is the military junta losing control? - Sandeep Singh (2024)
The recent activation of an existing conscription law in Myanmar by the ruling military junta seeks to draft young people into serving in the military in a situation of worsening civil conflict in the country. This significant development was in response to increased gains by rebel forces and demonstrates the shaky position of the junta.